2018
DOI: 10.1177/0004563218812986
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive fluorescence method for detecting urine formaldehyde in patients with Alzheimer’s disease

Abstract: Background Morning urine formaldehyde concentrations could predict the severe degree of dementia in patients with post-stroke dementia and Alzheimer’s disease. However, the routinely available technique of high-performance liquid chromatography (HPLC) for detecting urine formaldehyde requires expensive and sophisticated equipment. Methods We established a fluorescence spectrophotometric method by using a formaldehyde-specific fluorescent probe-NaFA (λex/em = 430/543 nm). As a standard reference method, the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…To elucidate the relationship between cerebellar formaldehyde levels and motion functions under weightless conditions, we first made a mouse model of HU stress by subjecting the hind limbs to unloading for 2 consecutive weeks as described previously 10 , 19 , 20 , and then examined the formaldehyde concentrations in the brain and assessed motor behaviors. Using an in vivo small animal imaging system with the free formaldehyde fluorescence probe NaFA ( λ ex/em = 440/550 nm) 21 , 22 (Fig. 1a ), we found that HU-stress induced a time-dependent elevation in the fluorescence intensity due to cerebellar formaldehyde (values on day 7 vs. day 0: n = 6, t = 7.827, df = 10, p < 0.001; values on day 14 vs. day 0: n = 6, t = 11.43, df = 10, p < 0.001; one-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate the relationship between cerebellar formaldehyde levels and motion functions under weightless conditions, we first made a mouse model of HU stress by subjecting the hind limbs to unloading for 2 consecutive weeks as described previously 10 , 19 , 20 , and then examined the formaldehyde concentrations in the brain and assessed motor behaviors. Using an in vivo small animal imaging system with the free formaldehyde fluorescence probe NaFA ( λ ex/em = 440/550 nm) 21 , 22 (Fig. 1a ), we found that HU-stress induced a time-dependent elevation in the fluorescence intensity due to cerebellar formaldehyde (values on day 7 vs. day 0: n = 6, t = 7.827, df = 10, p < 0.001; values on day 14 vs. day 0: n = 6, t = 11.43, df = 10, p < 0.001; one-way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…3 b, c ), which was detected by a mitochondrial formaldehyde-sensitive fluorescence probe ( λ ex/em = 440/550 nm) 29 and a Ca 2+ -sensitive probe Fura-2 AM, respectively 30 . Meanwhile, we observed the effects of microgravity on cytoplasmic formaldehyde as quantified by a free formaldehyde fluorescence probe 22 . Our results indicated that the cultured neuronal cells exhibited marked elevations in the levels of intracellular Ca 2+ ( n = 18, t = 5.027, df = 34, p < 0.0001; unpaired t -test) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence derivatisation methods [ 20 23 ] are based upon reactions forming compounds possessing fluorescence properties. These include reaction of aldehydes with β -diketones (Hantzsch reaction), such as 2,4-pentanedione [ 34 ] and 1,3-cyclohexanedione [ 35 ], Fluoral-P [ 36 39 ], anthrone [ 40 ], m-aminophenol [ 41 ], and ampicillin [ 21 ], with the latter showing lack of selectivity [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most prevalent type of dementia and is characterized by the progressive decline, and ultimately, loss of multiple cognitive functions (Ai et al, 2019;Das et al, 2019). The characteristic pathologic hallmarks, including neuritic plaques, synaptic loss (Katsouri et al, 2015), neurofibrillary tangles, and deposits of Aβ have been observed in the brain of AD patients (Granadillo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%